ANALYSIS OF THE NUMERICAL ABILITY OF ELEMENTARY SCHOOL STUDENTS IN TERMS OF GENDER DIFFERENCES - Umar; Arif Widodo (Sean Institute, 2022)
Numeracy is one of the basic skills for students is still a serious problem that has not been resolved in elementary schools. Not a few elementary school students have difficulty understanding basic numeracy material. Teachers are required to always innovate so that numeracy learning is easier for students to understand. This study aims to analyze stu dents' numeracy ability in terms of students' gender differences. Through this research, it is hoped that teachers will have a reference as an evaluation material in determining treatment to improve students' numeracy ability. This research was designed in the form of qualitative descriptive research. Data collection using tests. The tests used are in the form of an ability to recognize place value and a basic arithmetic operation ability test. Data collection was carried out at one of the public elementary schools in the Central Lombok district. The subjects in this study were 78 elementary school students consisting of 30 male students and 48 female students. The results showed that there were differences in numeracy ability between male and female students. The numeracy ability of female students is higher than that of male students. Boys tend to lag behind female students in terms of basic numeracy ability. Female students dominate at high-level numeracy ability while male students only dominate at low-level numeracy abilities.